Incidence of Posteromedial Meniscocapsular Separation and the Biomechanical Implications on the Anterior Cruciate Ligament. Issue 4 (15th February 2019) - Edgar, Cory; Kumar, Neil; Ware, James K.; Ziegler, Connor; Reed, Dale N.; DiVenere, Jessica; Obopilwe, Elifho; Cote, Mark P.; Arciero, Robert A.
Abstract : Purpose: To report the incidence of posterior medial meniscocapsular junction (PMCJ) separation in patients with anterior cruciate ligament (ACL) injury and to evaluate its biomechanical effect on the ACL. Methods: Three hundred thirty-seven consecutive patients undergoing isolated primary ACL reconstruction were retrospectively analyzed for PMCJ lesion. Forty-four patients were identified with PMCJ lesion and studied. Eight cadaver knees underwent biomechanical testing to determine anterior tibial displacement and anteromedial bundle ACL strain in the intact, PMCJ lesion, and PMCJ repair states at 0°, 30°, 60°, and 90° of flexion. Mixed-effects linear regression with Bonferroni correction was used for statistical analysis. Results: PMCJ tear incidence with ACL disruption was 13.1%. Specimen with PMCJ tears had statistically increased anterior tibial translation at 30° (1.2 mm; P < 0.01) and statistically increased ACL strain at 30° (24%; P < 0.01) and 90° (50%; P < 0.01). With PMCJ repair, translation reduced ( P > 0.05) by 12%, 18%, and 10% at 0°, 30°, and 90° of flexion, respectively. PMCJ repair reduced ( P < 0.05) ACL strain by 40%, 39%, 43%, and 31% at 0°, 30°, 60°, and 90° of flexion, respectively. Conclusions: A PMCJ lesion was observed in 13% of ACL injuries. This injury contributes to increased ACL strain, and PMCJ repair markedly reduces ACL strain to preinjury levels.